Preparation, characteristics and mechanisms of the composite sintered bricks produced from shale, sewage sludge, coal gangue powder and iron ore tailings. (30th January 2020) - Luo, Liqun; Li, Keyao; Fu, Weng; Liu, Cheng; Yang, Siyuan
Graphical abstract: Highlights: Iron ore tailings and coal gangue were used to prepare the composite sintered bricks. Sewage sludge and shale could be applied as the binder for the brick-marking. The properties of sintered bricks met the requirement of bearing bricks. The organic matter and water determined the mass and energy changes during sintering. The brick strength was increased by the molten glass phase wrapped crystal particles. Abstract: Iron ore tailings and coal gangue powder are the main sources of industrial solid wastes, the dispose of which has become severe and urgent with the increasing demand of environmental harmony. The present study firstly proposed a reasonable way to deal with the large amount of iron ore tailings and coal gangue powder by making them as the sintered bricks with sewage sludge and shale as the binder, considering the advantages in both economic and environmental aspects. The bulk density, sintering shrinkage, water absorption and compressive strength of the composite sintered bricks were tested to determine the optimum preparation conditions, including sludge content, molding pressure, sintering temperature and holding time. The aforementioned characteristics as well as the leaching toxicity of composite sintered bricks produced under the optimum conditions were all met the requirement of Chinese standard of bearing-brick. Thermogravimetry and differential scanning calorimetry (TG-DSC) were applied to reveal the phase transition of components during the sintering process. It was found that most of the mass and energy changes were caused by the phase transition of organic matter and water. The scanning electron microscopy (SEM) found that the section of unburned brick has discrete particles with disordered size and arrangement. During the sintering process, the newly generated crystal-like mineral particles significantly increased, and the molten glass phase also appeared to wrap and cement these tiny crystal-like particles, resulted into the increasing compressive strength of sintered brick.